Archie J. Bahm: Epistemotogy: Theory of Knowledge. World Books. Albuquerque, New Mexico 1995. 261+VI pp. - Bahm, A. (Tópicos, Revista de Filosofía, 2013)
Archie J. Bahm: Epistemotogy: Theory of Knowledge. World Books. Albuquerque, New Mexico 1995. 261+VI pp.